26 ANALISIS KELUHAN RASA SAKIT PEKERJA DENGAN MENGGUNAKAN METODE REBA DI STASIUN PENJEMURAN - Michella Hasibuan; Anizar M.kes; Sugih Arto P (Departemen Teknik Industri Universitas Sumatera Utara, 2014)
UD. ABC is one of the small industries engaged in the manufacture of white crackers. The condition in drying station is a facility that is not ergonomic and static posture workers. Workers had complaints of pain in several parts of his body. Sick workers are perceived as hunched position (300) is currently drafting up a nest crackers (crackers drying container). Parts of the body have a very sick sense that the knees and feet. This pain is felt because of the position of the foot is not balanced (bending> 600) and work facilities that do not fit so make frequent leg cramps. REBA method used to assess the posture of the workers. Analysis of REBA worksheet shows a high level of risk experienced by workers during the production activities that take place in the drying station. The results of design study work facilities are table and chair that are tailored to the dimensions of the body, so that implemented is expected to eliminate the pains felt by workers.